2003
DOI: 10.1128/aem.69.6.3412-3420.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of Biofilms in Dental Unit Water Systems

Abstract: We investigated the microbial diversity of biofilms found in dental unit water systems (DUWS) by three methods. The first was microscopic examination by scanning electron microscopy (SEM), acridine orange staining, and fluorescent in situ hybridization (FISH). Most bacteria present in the biofilm were viable. FISH detected the ␤ and ␥, but not the ␣, subclasses of Proteobacteria. In the second method, 55 cultivated biofilm isolates were identified with the Biolog system, fatty acid analysis, and 16S ribosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 33 publications
5
72
0
7
Order By: Relevance
“…An important aspect of this approach was a requirement for the bacteria to continue to survive and replicate following staining by the dyes. Traditional nucleic acid stains, such as acridine orange, hexidium iodide, and Hoechst 33342, have been used to stain multiple species of planktonic and biofilm bacteria for visualization using standard fluorescent microscopy (21,46) and confocal laser scanning microscopy (10,27). However, generally these have been used as terminal analytical approaches for bacterial counts and/or viability (30,45) or to provide an evaluation of bacterial aggregation onto solid surfaces (10, 27) with minimal assessment for visualizing and maintaining cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of this approach was a requirement for the bacteria to continue to survive and replicate following staining by the dyes. Traditional nucleic acid stains, such as acridine orange, hexidium iodide, and Hoechst 33342, have been used to stain multiple species of planktonic and biofilm bacteria for visualization using standard fluorescent microscopy (21,46) and confocal laser scanning microscopy (10,27). However, generally these have been used as terminal analytical approaches for bacterial counts and/or viability (30,45) or to provide an evaluation of bacterial aggregation onto solid surfaces (10, 27) with minimal assessment for visualizing and maintaining cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Singh et al (10) in 2003, the main techniques used was advanced fluorescent in situ hybridization (FISH) and electron microscopy. They investigated the biofilm obtained from dental unit water lines (DUWL) and reported that the high contamination prevalence in dental unit water samples could be the result of high amounts of microbial biofilms enriched with bacteria along the narrow waterlines of these units.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to previous studies. 22,23 Sphingomonas paucimobilis was reported to cause outbreaks of bacteremia among immunocompromised patients in hematology and oncology units due to bacterial contamination of hospital water systems. 24 It is now emerging as an opportunistic pathogen that is frequently reported in clinical settings.…”
Section: Sphingomonas Paucimobilismentioning
confidence: 99%